PENGARUH MANAJEMEN LABA, PROFITABILITAS, DAN INFLASI TERHADAP RETURN SAHAM (STUDI PADA PERUSAHAAN INDEKS LQ45 DI BEI TAHUN 2018-2020) - Winda Putri, Ni Putu Melina; Badjra, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.05.TAHUN.2023DO - 10.24843/EEB.2023.v12.i05.p18, 2023)
This study aims to determine the effect of earnings management, profitability, and inflation on stock return. The population in this study are companies on the LQ45 index company on the Indonesia Stock Exchange in 2018-2020. The sample in this study is 30 companies that always appear as members of LQ45 on the Indonesia Stock Exchange from 2018-2020 and have complete data related to research variables determined based on the purposive sampling method. The data analysis technique used is descriptive statistics and inferential statistics. The results of this study indicate that earnings management and inflation have a negative effect on stock return, while profitability has no effect on stock return.